KORUPSI DI INDONESIA DITINJAU MENURUT HUKUM EKONOMI SYARIAH - Syarbaini, Ahmad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
Corruption is a very old human culture. The term corruption comes from the Latin coruptio and corruptus which means to bribe and corrumpere means to damage. Corruption is: "A mistake made by someone either in the economy, intellectual or political". Corruption is a sinful act which is included in jarimah, the punishment for which is ta'zir. Corruption in Indonesian law is: "Unlawfully carrying out acts of enriching oneself or others or a corporation that can harm state finances or the state economy". Here are some reasons why corruption is considered an extraordinary crime that can destroy the state economy and sharia economy: First; Corruption causes great and widespread damage, second; corruption is a systemic crime, third; corruption violates human rights, fourth; Corruptors are punished severely, fifth; corruption threatens world order, and sixth; corruption damages the sharia economy.